A Possible Link between Anxiety and Schizophrenia and a Possible Role of Anhedonia. (17th January 2018) - Grillo, Luigi
Abstract : In the prodromal phase of schizophrenia, severe alterations of the visual appearance of the environment have been found, accompanied by a state of intense anxiety. The present study considers the possibility that these alterations really exist in the appearance of objects, but that healthy people do not see them. The image of the world that we see is continuously deformed and fragmented by foreshortenings, partial overlapping, and so on and must be constantly reassembled and interpreted; otherwise, it could change so much that we would hardly recognize it. Since pleasure has been found to be involved in visual and cognitive information processing, the possibility is considered that anhedonia (the reduction of the ability to feel pleasure) might interfere with the correct reconstruction and interpretation of the image of the environment and alter its appearance. The possibility is also considered that these alterations might make the environment hostile, might at times evoke the sensation of being trapped by a predator, and might be the cause of the anxiety that accompanies them. According to some authors, they might also induce delusional ideas, in an attempt to restore meaning in a world that has become chaotic and frightening.